Transcriptomic insights into the molecular mechanism for response of wild emmer wheat to stripe rust fungus - Ren, Jing; Chen, Liang; Liu, Jian; Zhou, Bailing; Sha, Yujie; Hu, Guodong; Peng, Junhua (Frontiers in Plant Science, 2024)
Continuous identification and application of novel resistance genes against stripe rust are of great importance for wheat breeding. Wild emmer wheat, Triticum dicoccoides, has adapted to a broad range of environments and is a valuable genetic resource that harbors important beneficial traits, including resistance to stripe rust caused by Puccinia striiformis f. sp. tritici (Pst). In the present study, we conducted an investigation into the genome-wide transcriptome profiles of two distinct genotypes of wild emmer wheat, DR3 exhibiting moderate Pst resistance, and D7 displaying high Pst resistance). A total of 16,659 genes were identified as differentially expressed in response to Pst infection. The number of differentially expressed genes in DR3 was found to be significantly higher than in DR7 at both 24 and 72 hours post-inoculation (hpi). However, it was observed that more pathways were enriched in DR7 compared to DR3, indicating a significant difference in Pst-response between the two genotypes. Remarkably, there were consistent patterns in the enrichment of pathways between the two genotypes at the same time of inoculation. At 24 hpi, a majority of pathways such as the biosynthesis of secondary metabolites, phenylpropanoid biosynthesis, phenylalanine metabolism, and alpha-Linolenic acid metabolism exhibited significant enrichment in both genotypes. At 72 hpi, the biosynthesis of secondary metabolites and circadian rhythm-plant pathways were notably and consistently enriched in both genotypes. Additionally, numerous transcription factors were found to be involved in the response to the Pst infection, and and distinct patterns of gene expression were observed within specific families at different time points following Pst inoculation. The majority of WRKY, MADs, and AP2-ERF families were found to be involved in the initial stage of response to Pst invasion (24 hpi), while the MYB, NAC, TCP, and b-ZIP families played a role in defense during the later stage of Pst infection (72 hpi). Our findings offer valuable information for understanding the function of crucial Pst-responsive genes, and will deepen the understanding of the complex resistance mechanisms against Pst in wheat.